PERAN SERIKAT PEKERJA DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Yuhari Robingu (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
Right to unite freely gather and expel opinion is a human rights. This right in Indonesia has receive law guarantee as has been stated in article 28 e paragraph (3) UUD 1945 which stated that “Every person has a right to unite, gather and expel opinion freely.